Caring for Stepparents in Later Life - Suzanna Smith (EDIS)
“Most people agree with the idea that families have a responsibility to care for older family members. Yet some changes in family life have brought up new questions about caring for the elderly. What happens when a parent divorces and then remarries later in life? Should adult children care for the stepparent as well as the parent? These questions are becoming more and more important as individuals live longer and growing numbers of older adults divorce and remarry…” This transcript of a two-minute Family Album Radio broadcast was published by the UF Department of Family, Youth and Community Sciences, March 2012.